Managing Raw Materials for a Synthetic Leather Company Using Material Requirement Planning (Case Study: PT.XYZ) - Faridah Farah Hapsari; R.B Seno Wulung (Universitas Muhammadiyah Mataram, 2023)
PT XYZ is a company engaged in the synthetic leather manufacturing industry. PT XYZ often lacks raw materials which results in the production process not running smoothly and even stops. This is due to the company's production planning which still uses forecasting methods. The purpose of this research is to be able to control the supply of raw materials to prevent production delays. The method used is MRP (Material Requirement Planning) with the aim of knowing the amount and time of raw materials that must be available for the smooth production process. The results showed that with the MRP method, the company can provide raw materials for production appropriately and have good information about the time to order raw materials so as not to experience a shortage of raw materials in inventory.